Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO270 - Sebastian Lindhorst; Maike Artschwager; Prithivi Dass Bissessur; Linus Budke; Benjamin Eberhardt; Jan Oliver Eisermann; Anna-Lena Geßner; Thomas Lüdmann; Ilona Schutter (PANGAEA, 2023)
Multibeam bathymetry raw data using the ship extquotesingles own Kongsberg EM 122 multibeam echosounder was almost continuously recorded during RV SONNE cruise SO270. Data was recorded on 40 days between 2019-09-13 and 2019-10-22. This dataset contains an elongated transit survey in the Indian Ocean over the Mid-Idian Ocean Basin also crossing the Fuji Seamount (mainly deep sea area extquotesingles). In addition, this dataset contains survey data from the Saya de Malha Bank and Sommerville Bank with shallow water depth. The approximate average depth of the entire dataset is around 4100m. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. Ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus SVP files are added to this dataset. Also data analysis of the multibeam raw data revealed that SVP has been changed during the survey. This publication is conducted within the efforts of the German Marine Research Alliance in the core area extquotesingleData management and Digitalization extquotesingle (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore contains incorrect depth measurements (artifacts) without further processing. Note that refraction errors can be expected due to the lack of proper SVP. Overall, it appears that the data quality is rather good since the gridded hillshade data showed relatively few obstacles. Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).